SOCIOSPATIAL SEGREGATION AND URBANIZATION IN PORTO VELHO, CANDEIAS DO JAMARI AND ARIQUEMES: A CRITICAL REVIEW - Gobira, Gilmar Celestino (Seven Editora, 2025)
This article addresses socio-spatial inequalities and the challenges of urbanization in the city of Porto Velho, located in the Brazilian Amazon. The objective of this work is to conduct a literature review on urban expansion and socio-spatial inequality in the western Amazon, involving the municipalities of Porto Velho, Candeias do Jamari, and Ariquemes. The study was conducted through a literature review based on 16 studies published between 2015 and 2025 found in the Google Scholar and BDTD databases. The results indicate that urbanization in the municipalities occurred in a disorderly manner, driven by economic cycles and exogenous political decisions, resulting in irregular settlements, lack of infrastructure, and social exclusion. The study reinforces the importance of integrated public policies that are sensitive to regional specificities.DOI: https://doi.org/10.56238/sevened2025.029-033